2021
DOI: 10.1002/glia.24019
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with hypoxia‐mimetics protects cultured rat Schwann cells against oxidative stress‐induced cell death

Abstract: Schwann cell (SC) grafts promote axon regeneration in the injured spinal cord, but transplant efficacy is diminished by a high death rate in the first 2–3 days postimplantation. Both hypoxic preconditioning and pharmacological induction of the cellular hypoxic response can drive cellular adaptations and improve transplant survival in a number of disease/injury models. Hypoxia‐inducible factor 1 alpha (HIF‐1α), a regulator of the cellular response to hypoxia, is implicated in preconditioning‐associated protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 88 publications
(201 reference statements)
2
18
0
Order By: Relevance
“…1 F exhibited cell viability of RSCs on the membrane at 24 ​h. The viability of RSCs on PDPLA/DFO electrospun films was significantly improved, which may be attributed to the pharmacological induction of hypoxia adaptation to promote the survival of transplanted RSCs [ 36 ]. The results showed that both PDPLA and PDPLA/DFO were suitable for adhesion and growth of Schwann cell and possessed good cyto-compatibility.…”
Section: Resultsmentioning
confidence: 99%
“…1 F exhibited cell viability of RSCs on the membrane at 24 ​h. The viability of RSCs on PDPLA/DFO electrospun films was significantly improved, which may be attributed to the pharmacological induction of hypoxia adaptation to promote the survival of transplanted RSCs [ 36 ]. The results showed that both PDPLA and PDPLA/DFO were suitable for adhesion and growth of Schwann cell and possessed good cyto-compatibility.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen deprivation model (OGD) was performed using the human neuroblastoma SH-SY5Y cell line. We chose adaptaquin as a control compound for the group of branched oxyquinolines since it showed neuroprotection in the post-treatment of hemorrhagic stroke in vivo model [ 20 ] and oxidative stress in vitro model at 1 μM concentration [ 21 , 22 ]. The experimental design was the same as we used before for the drugs targeting HIF PHD, Nrf2, and HDAC6, which showed almost complete neuroprotection at 24 h pretreatment in the range of concentrations matching the IC 50 in the HIF1 ODD-luc and Neh2-luc reporter assays [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neuradapt was shown to be neuroprotective in a hypoxia model in the hippocampal neuronal network [ 10 ]. Adaptaquin, a branched-tail oxyquinoline inhibitor discovered earlier [ 8 ], is neuroprotective in in vivo models of hemorrhagic stroke [ 20 ] and Parkinson’s disease [ 32 ], and against oxidative stress in vitro models [ 21 , 22 ]. There are studies demonstrating that neuroprotection exerted by adaptaquin in vivo is not HIF dependent [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has indicated that the atorvastatin-induced upregulation of miR-221-3p in MSC-EVs results in the recovery of endothelial cell function, thus alleviating diabetic skin defects [ 138 ]. As a hypoxia-mimic compound, deferoxamine can activate a HIF-1α signaling pathway [ 139 ]. Compared with natural MSC-EVs, diabetic rats treated with EVs secreted by deferoxamine-stimulated MSC exhibit enhanced angiogenic activity [ 140 ].…”
Section: Engineered Msc-evs In the Treatment Of Dm And Diabetic Compl...mentioning
confidence: 99%